Loss of Visual Acuity after Successful Surgery for Macula-On Rhegmatogenous Retinal Detachment in a Prospective Multicentre Study - Salvatore Di Lauro; Melissa Castrejón; Itziar Fernández; Jimena Rojas; Rosa M. Coco; María R. Sanabria; Enrique Rodríguez de la Rua; J. Carlos Pastor (Journal of Ophthalmology)
Purpose. To quantify the frequency of visual loss after successful retinal detachment (RD) surgery in macula-on patients in a multicentric, prospective series of RD. Methods. Clinical variables from consecutive macula-on RD patients were collected in a prospective multicentric study. Visual loss was defined as at least a reduction in one line in best corrected visual acuity (VA) with Snellen chart. The series were divided into 4 subgroups: (1) all macula-on eyes (n=357); (2) macula-on patients with visual loss at the third month of follow-up (n=53) which were further subdivided in (3) phakic eyes (n=39); and (4) pseudophakic eyes (n=14). Results. Fifty-three eyes (14.9%) had visual loss three months after surgery (n=39 phakic eyes; n=14 pseudophakic eyes). There were no statistically significant differences between them regarding their clinical characteristics. Pars plana vitrectomy (PPV) was used in 67.2% of cases, scleral buckle in 57.7%, and scleral explant in 11.9% (36.1% were combined procedures). Conclusions. Around 15% of macula-on RD eyes lose VA after successful surgery. Development of cataracts may be one cause in phakic eyes, but vision loss in pseudophakic eyes could have other explanations such as the effect of released factors produced by retinal ischemia on the macula area. Further investigations are necessary to elucidate this hypothesis.